Return Migration of the Highly Skilled in Higher Education Institutions: a Chinese University Case. Issue 8 (24th April 2014) - Wang, Qingfang; Tang, Li; Li, Huiping
Abstract: The war for 'global talents' becomes increasingly fierce worldwide with the thriving of knowledge‐based new economy. Many countries are implementing new initiatives to encourage their citizens trained overseas to return with their globalised work competencies. Although previous studies have identified various factors related to return migration, very few studies have focused on the return migration of academics, and more specifically, the role of the higher education institution (HEI) in the return migration process. Using both statistical analyses of micro‐data and in‐depth interviews, this study examines the HEI recruitment process through an extensive case study in a research university in China. We find that, for successful recruitment of overseas top talents, it is extremely important as to how university presents itself in the international stage of the global higher education markets. Meanwhile, we cannot underestimate the role of economic incentives. We also find that the role of networking is more subtle than what traditional migration theories would have predicted. Our findings provide important policy implications for practices regarding talent recruitment at the institutional level, particularly for those universities at the lower end of the global higher education hierarchy. Copyright © 2014 John Wiley & Sons, Ltd.